2017
DOI: 10.4049/jimmunol.1601693
|View full text |Cite
|
Sign up to set email alerts
|

T Cells in Celiac Disease

Abstract: Celiac disease is a human T cell mediated autoimmune-like disorder caused by exposure to dietary gluten in genetically predisposed individuals. This review will discuss how a CD4 T cell responses directed against an exogenous antigen can cause an autoreactive B-cell response and participate in the licensing of intraepithelial lymphocytes to kill intestinal epithelial cells. Furthermore, the review will examine the mechanisms by which intraepithelial cytotoxic T cells mediate tissue destruction in celiac diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
183
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 208 publications
(199 citation statements)
references
References 119 publications
(173 reference statements)
11
183
0
5
Order By: Relevance
“…However, these cells are restricted to the lamina propria and do not seem to directly cause disease pathology 109 . By contrast, conventional CD8αβ + TCRαβ + IEL populations are markedly expanded and activated but do not seem to be gluten specific 108 . In healthy individuals, conventional CD8αβ + TCRαβ + IELs express inhibitory NK cell receptors including CD94–NKG2A 110,111 , whereas in patients with coeliac disease, increased levels of IL-15 upregulate the expression of activating NK cell receptors including NKG2C and NKG2D.…”
Section: Human Diseasesmentioning
confidence: 87%
See 1 more Smart Citation
“…However, these cells are restricted to the lamina propria and do not seem to directly cause disease pathology 109 . By contrast, conventional CD8αβ + TCRαβ + IEL populations are markedly expanded and activated but do not seem to be gluten specific 108 . In healthy individuals, conventional CD8αβ + TCRαβ + IELs express inhibitory NK cell receptors including CD94–NKG2A 110,111 , whereas in patients with coeliac disease, increased levels of IL-15 upregulate the expression of activating NK cell receptors including NKG2C and NKG2D.…”
Section: Human Diseasesmentioning
confidence: 87%
“…Coeliac disease is an inflammatory disorder in which a subset of genetically susceptible individuals who express HLA-DQ2 or HLA-DQ8 develop T H 1 cell-type inflammation in the small intestine, leading to villous atrophy and subsequent nutrient malabsorption 108 . Massive expansion of intestinal IEL populations is a hallmark of the disease.…”
Section: Human Diseasesmentioning
confidence: 99%
“…The use of acute single‐dose oral food challenge is well established as an informative diagnostic manoeuvre and trial monitoring approach for food allergy, but has not previously been shown to be useful in coeliac disease . Coeliac disease is caused by ingestion of dietary gluten and activation of gluten‐specific CD4 + T cells; chronic gluten exposure results in characteristic histological abnormalities in the duodenal mucosa and production of autoantibodies specific for transglutaminase . Symptoms caused by gluten in coeliac disease are generally considered nonspecific, and delayed for days or weeks after gluten is reintroduced into the diet .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Coeliac disease is caused by ingestion of dietary gluten and activation of gluten-specific CD4 + T cells; chronic gluten exposure results in characteristic histological abnormalities in the duodenal mucosa and production of autoantibodies specific for transglutaminase. 3 Symptoms caused by gluten in coeliac disease are generally considered nonspecific, and delayed for days or weeks after gluten is reintroduced into the diet. 4,5 Thus, acute provocation testing has not played a role in the diagnosis of coeliac disease.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the overall effectiveness of the method in identifying condition-associated CDR3s, we looked closely at the set of differentially enriched CDR3βs and compared them to known celiac disease associated CDR3β sequences in the literature. The detected lists of enriched CDR3βs had significantly increased usage of previously reported TRBV-genes in gluten-reactive CDR3β sequences (Qiao et al, 2011(Qiao et al, , 2013Broughton et al, 2012;Jabri and Sollid, 2017;Han et al, 2013) (Qiao et al, 2011(Qiao et al, , 2013 (Figure 5c and d, Figure 3Sc and d) , the method identified other previously unreported over used genes such as TRBV03-01 with previously unappreciated per-position amino acid usage patterns in the detected enriched CDR3s (Figure 5c), the detailed analysis of which may provide insights on their targets and overall significance in the pathogenesis of celiac disease. In addition, except in the nucleotide subsequence based analysis of CD Gut, the list of enriched CDR3βs from both CD PBMC and CD Gut contained significantly high number of previously reported CD-associated CDR3β sequences by Qiao et al, Han et al and Petersen et al (Qiao et al, 2011;Han et al, 2013;Petersen et al, 2014) than was expected by chance, as determined by both using a randomization test or a straight forward comparison to the proportion of previously known celiac disease associated CDR3s in the total repertoire of the combined dataset of all samples (see Tables 2 and 3, see supplementary Tables 1S and 2S for the list of previously known celiac disease associated CDR3 identified by the method).…”
Section: Resultsmentioning
confidence: 72%